Evaluasi Penerapan Nesting Terhadap Perubahan Berat Badan dan Tanda Vital Bayi: Evaluation of Nesting Implementation on Weight Change and Vital Signs of Infants Infant Vital Signs - Melania Fitri Astuti; Lina Dewi Anggraeni; Sada Rasmada (NERS Jurnal Keperawatan, 2022)
Application of nesting is one of the independent actions of nurses in helping newborns adapt to their new environment. Nesting can be applied to all newborns regardless of birth weight or gestational age. This study aims to evaluate the application of nesting on infant weight and vital signs at X Hospital Jakarta. This study involved 318 samples with purposive sampling technique, pre-experimental research design one group pre posttest design. Data obtained from medical records. Data analysis used paired T test, which showed that there was a change in the baby's weight on the nesting application (p value= 0.014), there was a change in vital signs on the nesting application (HR (p value =0.000); RR (p value =0.000); SaO2 (p value = 0.000)). The application of nesting is beneficial for newborns, namely maintaining the stability of the baby's vital signs, and increasing body weight. The recommendation that can be given is to maintain the application of nesting as a baby care needs.